2022
DOI: 10.3390/coatings12030367
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Performance of Ni/TiN Coatings Deposited by Laser Melting Deposition on 40Cr Substrates

Abstract: The current study reports the successful preparation of Ni/TiN coatings via laser melting deposition (LMD) for repairing the shaft of an electric submersible pump (ESP). The surface morphology, microstructure, phase composition, microhardness, shear strength, and wear resistance were investigated using a scanning electron microscope (SEM), X-ray diffractometer (XRD), microhardness meter, shear strength test machine, and friction and wear tester. Among the three coatings, the Ni/TiN coating deposited at 1.5 kW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Based on the experimentation conducted, it was observed that the microhardness values of Ni-GO nanocomposite coating varied depending on the roughness of the substrate surface. These findings suggest that the smooth substrate provides a higher microhardness value, indicating better mechanical properties and potentially improved performance of the coating [12]. This information is important as it suggests that optimizing the smoothness of the substrate surface can lead to improved mechanical properties and performance of the Ni-GO nanocomposite coating.…”
Section: Microhardness Of Coatingsmentioning
confidence: 87%
“…Based on the experimentation conducted, it was observed that the microhardness values of Ni-GO nanocomposite coating varied depending on the roughness of the substrate surface. These findings suggest that the smooth substrate provides a higher microhardness value, indicating better mechanical properties and potentially improved performance of the coating [12]. This information is important as it suggests that optimizing the smoothness of the substrate surface can lead to improved mechanical properties and performance of the Ni-GO nanocomposite coating.…”
Section: Microhardness Of Coatingsmentioning
confidence: 87%
“…However, the surface will fail and the service life will be seriously reduced in the working environment such as wear, tear and corrosion for a long time [3,4]. Therefore, it is necessary to modify the surface of 40Cr steel by adding alloy elements [5,6]. As a solid solution element, Ni is usually dissolved in ferrite or austenite and plays a role in solid solution strengthening [7].…”
Section: Introductionmentioning
confidence: 99%